37 The differences in rate of inversion and perceived instability during a dynamic perturbation in those with and without cai. (12th October 2015) - Hall, EA; Simon, JE; Docherty, CL
Abstract : Background: Following a lateral ankle sprain, residual symptoms such as pain, weakness, and perceived instability can occur. Objective: To determine differences in rate of inversion and perceived ankle instability during a dynamic perturbation in individuals with and without chronic ankle instability (CAI). Design: Crossover study. Setting: Laboratory. Patients (or participants): Thirty-six participants volunteered and were divided into two groups: CAI (n = 16, age = 19.8 ± 0.9 years, height = 165.7 ± 7.0 cm, body mass = 65.5 ± 11.7 kg) and control (n = 20, age = 21.7 ± 3.6 years, height = 170.4 ± 10.6 cm, body mass = 65.3 ± 11.8 kg). The CAI group had a history of ankle sprains and scored ≥11 or higher on the IdFAI. The control group had no history of ankle sprains in either limb and scored zero on the IdFAI. Interventions: Participants walked down a custom-built 7.3 m walkway, which was designed with sections that suddenly inverted the subjects' ankles to 30° while wearing a standardised shoe. Main outcome measurements: Rate of inversion (°/s) was calculated by dividing maximum range of motion by the time to maximum inversion. Data were captured using an electrogoniometer (SG110/A, Biometrics, Ltd, UK) placed on the lateral aspect of the ankle. The average of three trials was used for statistical analysis. Perceived ankle instability was measured using a visual analogue scale. Participants marked a dash on a vertical 10-cm line to rate how unstable their ankle felt on the walkway. One-way ANOVA was performed on each dependent variable. The a priori alpha level was set at p < 0.05. Results: No significant difference in rate of inversion was observed between the groups (p = 0.70). There was a significant difference in perceived instability (p = 0.01, CAI group = 4.14 ± 2.48 cm, control group = 0.99 ± 1.3 cm). Conclusions: These results indicate that despite the similarities between groups in rate of inversion, participants in the CAI group still felt less stable than the control group during the dynamic inversion task.